Vitiligo detection capabilities of 1D photonic crystal biosensing design - Ali S. Alshomrany; Arafa H. Aly; B. A. Mohamed; S. Alamri; D. Mohamed; S K Awasthi; Zinab. S. Matar; A F Amin; H. Hanafy (Scientific Reports)
Abstract This theoretical work focuses on the application of Tamm resonance-based biosensing using a one-dimensional photonic crystal for detecting skin vitiligo, a condition caused by the loss of pigment in the body. This biosensor utilizes the interaction of light with the photonic structure to identify the specific biomarkers associated with vitiligo. The proposed structure is composed of prism/Ag/skin-sample/(GaP/PS)N/glass. The MATLAB simulations are used to obtain numerical results pertaining to the work by using the transfer matrix method (TMM). The analysis of transmission spectra of the proposed structure shows its minute sensing ability of detecting skin vitiligo. The proposed sensor possesses a higher sensitivity of 1200 nm/RIU which is higher than the sensitivities of the sensor reported earlier. Moreover, the suggested biosensor possesses an extremely high-quality factor value of 40,650 with an exceptionally small full-width-half-maximum value of 0.04 nm.